Increased price markup from union coordination: OECD panel evidence - Roger Bjørnstad; Kjartan Øren Kalstad (Economics: The Open-Access, Open-Assessment E-Journal, 2010)
Although coordination of wage bargaining probably affects entry barriers and competition in product markets, research on price determination has typically not considered such factors. We argue that the price markup depends on wage setting institutions and present empirical evidence in form of estimated price equations in a panel of 15 OECD countries. The estimates show that consumer prices may be as much as 21 percent higher in coordinated compared to uncoordinated countries, solely due to the effect of coordination on the markup. Since other studies find that coordination has a dampening effect on wages, this may explain why there is no clear effect of coordination on unemployment.
Keywords: C23; E31; J51; 330; Imperfect competition model; price markup; labor market institutions; unemployment; panel data model; Tarifpolitik; Lohnverhandlungen; Wirkungsanalyse; Mark-up Pricing; Konsumgütermarketing; Arbeitslosigkeit; Panel; Schätzung; OECD-Staaten